1998
DOI: 10.1111/j.1439-0450.1998.tb00764.x
|View full text |Cite
|
Sign up to set email alerts
|

Water as a Reservoir for Campylobacter jejuni Infection in Cows Studied by Serotyping and Pulsed‐field Gel Electrophoresis (PFGE)

Abstract: Ktb onefgnn and 2 tables (Rereiwedjrpnbbration Febtwary 5, 1997) SummaryThe occurrence of campylobacters was studied in the faecal samples of a dairy herd with about 20 animals and in the lake which was their source of drinking water during the grazing period from June to September. Of the total of 141 faecal samples studied, &21 Yo were found to be positive for C je/mi at various sampling times throughout the year. More cows were found to be campylobacter-positive in summer or in autumn after the grazing peri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
37
1

Year Published

2001
2001
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(44 citation statements)
references
References 16 publications
3
37
1
Order By: Relevance
“…Indeed, emptying and cleaning water troughs more regularly have been shown to reduce the risk of colonization of cattle by Campylobacter (334). Furthermore, it has been reported that cattle were more likely to test positive for Campylobacter following an outdoor grazing period in spring, when the water supply was lake water, than when they were confined indoors in winter, when their water supply was municipal chlorinated tap water (376). Other sources implicated in the contamination of outdoor water are wild bird feces and waste runoff from contaminated domesticated animals (377).…”
Section: Watermentioning
confidence: 99%
“…Indeed, emptying and cleaning water troughs more regularly have been shown to reduce the risk of colonization of cattle by Campylobacter (334). Furthermore, it has been reported that cattle were more likely to test positive for Campylobacter following an outdoor grazing period in spring, when the water supply was lake water, than when they were confined indoors in winter, when their water supply was municipal chlorinated tap water (376). Other sources implicated in the contamination of outdoor water are wild bird feces and waste runoff from contaminated domesticated animals (377).…”
Section: Watermentioning
confidence: 99%
“…(23,25) and are frequently mentioned as possible vectors for transmission to poultry (2,15,40), cattle (22), and humans (35,38,44). Campylobacter jejuni, the main human pathogen of the genus, is now recognized as a leading cause of acute bacterial gastroenteritis in many parts of the world (3,18).…”
mentioning
confidence: 99%
“…Improper cooking of chicken meat might lead to killing of superficially contaminating bacteria, while a strain in the inner parts of the food would be exposed to lower temperatures, thus being able to survive. Finally, those results could be explained by overestimation of poultry meat as a source of infection since simultaneous contamination with different strains has been demonstrated to a much lesser extent for other sources like raw milk and drinking water (7,11). However, this subject has not been studied in detail.…”
mentioning
confidence: 99%